Neurodegeneration in humans caused by prions. - Prusiner, S B (1994)
Prion diseases include kuru, Creutzfeldt-Jakob disease, Gerstmann-Sträussler-Scheinker disease, and fatal familial insomnia of humans as well as scrapie and bovine spongiform encephalopathy of animals. For many years, the prion diseases were thought to be caused by viruses despite evidence to the contrary. The unique characteristic common to all of these disorders, whether sporadic, dominantly inherited, or acquired by infection, is that they involve aberrant metabolism of the prion protein. In many cases, the cellular prion protein is converted into the scrapie variant by a process after translation that involves a conformational change. Often the human prion diseases are transmissible experimentally to animals, and all of the inherited prion diseases segregate with prion protein gene mutations.